Functional properties of extrasynaptic AMPA and NMDA receptors during postnatal hippocampal neurogenesis. (3rd December 2013) - Schmidt‐Salzmann, Charlotte; Li, Liyi; Bischofberger, Josef
Key points:   Extrasynaptic AMPA and NMDA receptors (AMPARs and NMDARs) were studied in newly generated young hippocampal granule cells at different stages of functional synaptic integration.   Whereas AMPAR density increased dramatically with cell maturation, the NMDAR current density was nearly constant, leading to an initially high NMDAR to AMPAR conductance density ratio.   AMPAR desensitization was slowest during the main phase of synapse formation and substantially faster before and afterwards at fully integrated mature stages.   Steady state current amplitude was also largest during synaptic integration and ∼50% smaller afterwards.   The data suggest that during periods of new synapse formation prolonged extrasynaptic AMPAR currents might support effective depolarization and NMDAR activation during spillover of glutamate. Abstract  In the mammalian hippocampus, new granule cells are continuously generated throughout life. Although it is well known that they rapidly form several thousand new glutamatergic synapses, the underlying mechanisms are not well understood. As extrasynaptic NMDA receptors are believed to support the generation of new spines, we have studied the functional properties of extrasynaptic ionotropic glutamate receptors in newborn granule cells in juvenile rats during and after synaptic integration. Using the fast application of glutamate to outside‐out membrane patches, we show that all immature granule cells express functional AMPA and NMDA receptors. The density of AMPA receptors was small in cells starting to receive excitatory synaptic input (∼30 pS μm −2 ) but substantially increased during synaptic integration to finally reach ∼120 pS μm −2 in fully mature cells. Interestingly, AMPA receptors showed a biphasic change in desensitization time constant which was slowest during synaptic integration and substantially faster before and afterwards. This was paralleled by a change in the non‐desensitizing current component which was maximal during synaptic integration and about 50% smaller afterwards. Surprisingly, the NMDA receptor kinetics and density in young cells was already comparable to mature cells (∼10 pS μm −2 ), leading to an enhanced NMDA/AMPA receptor density ratio. Similar to somatic outside‐out patches, iontophoretic application of glutamate onto dendrites also revealed an enhanced dendritic NMDA/AMPA ratio in young cells. These data indicate that prolonged AMPA receptor currents in newly generated young granule cells might support the effective activation of extrasynaptic NMDA receptors and therefore constitute a competitive advantage over mature cells for new synapse formation.